A novel ejector with a bypass to enhance the performance. (25th January 2016) - Chen, Weixiong; Chen, Huiqiang; Shi, Chaoyin; Xue, Kangkang; Chong, Daotong; Yan, Junjie
Highlights: A novel ejector with bypass is proposed to enhance the ejector performance. There is an optimal bypass inlet position to obtain the maximum entrainment ratio. The ejector performance with bypass installed in the optimal position is analyzed. Abstract: It is crucial to enhance the ejector capacity to widen its application in industry. A novel ejector with a bypass installed in the low pressure district is proposed to enhance the ejector capacity. The results show that there is an optimal position for the maximum entrainment ratio, which corresponds to the lowest pressure around the second shock position. When the ejector operates at design conditions (the primary/induced/back pressures are 0.3/0.02/0.08 MPa), the optimal length ratio is about 1.1. Then, the ejector performance with the optimal bypass is investigated under different operational parameters. It is found that the novel ejector has relatively high entrainment ratio and low critical back pressure compared to the ejector without bypass under the design condition. When the primary pressure is bigger than a certain value, the entrainment ratio would always improve as the primary or induced pressures increase.